Quantitative analysis of metallic artifacts caused by dental metals: Comparison of cone-beam and multi-detector row CT scanners - Jira Chindasombatjaroen (2018)
Objectives: To quantitatively compare the streak artifacts produced by dental metals in a cone-beam computed tomography (CBCT) device and a multi-detector row computed tomography (MDCT) scanner in relation to metal types and imaging parameters. Methods: Cubes of aluminum, titanium, cobalt-chromium alloy, and type IV gold alloy were scanned with CBCT and MDCT scanners at tube voltages of 80 and 100 peak kV (kVp), and currents of 100 and 170 mAs by MDCT, and 102 and 170 mAs by CBCT. Artifact areas were quantified using ImageJ software. Results: Artifact areas for the same metals and imaging parameters were smaller with CBCT than with MDCT under most conditions. Type IV gold alloy caused the largest artifact areas, followed by cobalt-chromium alloy, titanium, and aluminum, respectively. Higher tube voltage was associated with smaller artifact areas under most conditions, whereas increasing tube current had no consistent effect on artifact area using either CT device. Conclusions: CBCT was associated with smaller artifact areas than MDCT for the same parameters. Type IV gold alloy produced the largest artifact areas among the tested metals, but metallic artifacts could be reduced by increasing the tube voltage. © 2011 Japanese Society for Oral and Maxillofacial Radiology and Springer.